Fungsi Madrasah Diniyah Takmiliyah Awaliyah dalam Membentuk Karakter Religius Santri - Hasnul Fikri Nando; Ahmad Rivauzi (An-Nuha, 2022)
This study aims to determine the function of Madrasah Diniyah Takmiliyah Awaliyah in shaping the religious character of students in Nagari Pandam Gadang. This study uses a qualitative method with a case study research type. Researchers used data collection methods, namely interviews, observation, and documentation. Sources of data were taken from informants who were madrasa heads and teachers, as well as documents in the form of videos, photos and other documents. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of the research reveal that the function of Madrasah Diniyah Takmiliyah Awaliyah uses three theories, namely as a medium for learning religious teachings, as a vehicle for maintaining the values of religious teachings, and as a complement to Islamic Religious Education. These three theories are used as a reference in explaining the function of Madrasah Diniyah Takmiliyah Awaliyah in shaping the religious character of students in Nagari Pandam Gadang.